2022
DOI: 10.3389/fcvm.2022.923981
|View full text |Cite
|
Sign up to set email alerts
|

Modification effect of changes in cardiometabolic traits in association between kidney stones and cardiovascular events

Abstract: BackgroundsWhether longitudinal changes in metabolic status influence the effect of kidney stones on cardiovascular disease (CVD) remains unclarified. We investigated the modification effect of status changes in metabolic syndrome (MetS) in the association of kidney stones with risk of incident CVD events.MethodsWe performed a prospective association and interaction study in a nationwide cohort including 129,172 participants aged ≥ 40 years without CVDs at baseline and followed up for an average of 3.8 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Determining the exact prevalence of CHD or stroke from the different studies can be challenging. Xu [28] reports a CVD prevalence of 4.02% and a CHD prevalence of 1.44%, which is very close to ours. However, a 2.7% stroke prevalence was reported, which is significantly higher than our data.…”
Section: Discussionsupporting
confidence: 89%
“…Determining the exact prevalence of CHD or stroke from the different studies can be challenging. Xu [28] reports a CVD prevalence of 4.02% and a CHD prevalence of 1.44%, which is very close to ours. However, a 2.7% stroke prevalence was reported, which is significantly higher than our data.…”
Section: Discussionsupporting
confidence: 89%
“…Kidney stones (KS) are worldwide public health problem that impose a huge economic burden on patients and society [ 1 ]. KS lead to urinary tract infection and urinary obstruction, eventually causing renal function disability and renal insufficiency [ 2 ]. KS are caused by anomalous accumulation of crystalline materials (such as calcium oxalate, struvite stone and uric acid stone) in kidney, of which calcium oxalate (CaOx) is the most common and stands at 80% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that patients with a history of kidney stones have a signi cantly increased risk of cardiovascular diseases and fractures and are more likely to suffer renal hypofunction and eventually develop end-stage renal disease [4][5][6][7]. In addition, pain and other clinical manifestations during the onset of kidney stones seriously affect the daily work and quality of life of patients [8,9].…”
Section: Introductionmentioning
confidence: 99%